Determinant of Smoking Behavior at Home as a Clean and Healthy Life Behavior Effort in Puskesmas Nanjungmekar in 2019 - Kurniawati, Ratna Dian; Noorfarijan, Bintang Fathan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
PHBS Household itself is an effort so that families know, want and be able to maintain their own health in the health sector so as to avoid various risks of disease. The purpose of this study was to determine the determinants of smoking behavior in the home as an effort to clean and healthy behavior in the household setting in the working area of Nanjungmekar Health Center. The study design uses descriptive correlational with Cross Sectional approach. Sampling used Multistage Sampling as many as 96 households. The measuring instrument is a questionnaire with Chi-square analysis. The results showed that the majority (54.2%) of family heads behaved in the house smoking. There is a relationship of knowledge, attitudes, and the role of cadres with smoking behavior and there is no relationship between motivation and smoking behavior. So it is necessary to disseminate PHBS evenly throughout the work area of the puskesmas through increasing the performance of cadres in order to be more competent in carrying out their duties in order to increase the coverage of household PHBS in the work area of the Nanjungmekar Puskesmas.